Kindlin-3 and RASSF6 are probable biomarkers for predicting metastasis in cutaneous melanoma - Bozdogan, Onder; Guresci, Servet; Öcalan, Devrim; Bozdogan, Nazan (Polish Journal of Pathology, 2021)
It is well known that metastasis is the most crucial factor in determining the fate of the patient. The prognosis of melanoma is very poor at the stage of metastasis. Recently, several genes and proteins, including kindlin3, dioxin receptor (AhR), RASSF6, and claudin-11, which were shown as possible prognostic biomarkers for human tumours, were described. In this study, we focused on these proteins in melanoma within a clinical setting. Forty-three primary melanomas (PMs), 17 metastatic melanomas (MMs), 15 melanocytic nevi (MN), and two melanoma cell lines were included in this retrospective study. All proteins were investigated using immunohistochemistry, and analysis was performed using a semi-quantitative immunoreactive score (IRS). The nevus group showed lower RASSF6 and AhR IRS levels than PMs. RASSF6 and kindlin-3 levels in the PMs with metastasis (MwM) and also in PMs showing lymphovascular invasion were significantly lower. The logistic regression model also proved that kindlin-3 expression was a significant independent predictor of metastasis. The current study supports the role of kindlin-3 and RASSF6 as prognostic biomarkers in melanoma. Besides the prognostic roles of these proteins, they are probably potential candidates for target-oriented therapies for melanoma metastasis blocking.